Language Contact and the Emergence of Ethnically Oriented Varieties of English in Multilingual Nigeria (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2026)
This study examines language contact and the emergence of ethnically oriented varieties of English in multilingual communities, with particular emphasis on English as the focal language. It investigates the causes, effects, and outcomes of language contact, as well as the linguistic consequences arising from English interacting with other languages. Using Nigeria as a case study due to its highly multilingual nature, the study explores how sustained contact between English and indigenous languages has led to the development of distinct local and global varieties of English. The research adopts a qualitative descriptive approach and is theoretically anchored in Thomason and Kaufman’s (1988) Language Contact Theory. Data were presented and analyzed textually. Findings reveal that English has come into contact with numerous languages, resulting in the fusion of linguistic features and the emergence of multiple English varieties. The study identifies factors such as colonization, trade, war, intermarriage, tourism, and conquest as major drivers of language contact. These interactions have produced linguistic phenomena including multilingualism, code-mixing, code-switching, language shift, and language death. The findings further demonstrate that language contact brings significant changes to both indigenous and imported languages, with the degree of influence determined by the intensity of contact. The study concludes that language contact is a major catalyst for linguistic variation and multilingual practices and recommends the standardization and strengthening of indigenous languages to mitigate excessive external influence
Keywords: Language contact, Multilingualism, Ethnically oriented varieties of English, Code-mixing and code-switching, Indigenous languages